Pre-Release Preparation for Inmates at Class IIA Balikpapan Prison Through - Mardatillah Mardatillah; Novi Satria Jatmiko; Mira Suradi (Universitas AMIKOM Yogyakarta, 2025)
Psychological rights are one of the rights held by inmates the Class IIA Criminal Penitentiary Balikpapan, especially for those who will be released in the near future. And having a healthy mental health is an important point in the adjustment of inmates during parole or pure release, this is the point of the purpose of this community service. is to help prepare inmates. The method used is group counseling and individual counseling for 6 months or 1 semester from September to February. The results of this community service are counseling that takes place according to the purpose of this community service, namely preparing inmates for release so that they are more confident and adjust when in prison. The next obstacle is that counselors do not get specific and specific information from families only from inmates and correctional staff whose data is related to personal information. In addition, there are internal activities and events in prison.